2013
DOI: 10.4269/ajtmh.2012.12-0208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Loop-Mediated Isothermal Amplification Suitable for Molecular Monitoring of Schistosome-Infected Snails in Field Laboratories

Abstract: Abstract. We previously described loop-mediated isothermal amplification (LAMP) for detection of Schistosoma haematobium and S. mansoni DNA in infected snails. In the present study, we adapted the LAMP assay for application in field laboratories in schistosomiasis-endemic areas. Isolation of DNA was simplified by blotting snail tissue (extracted in NaOH/sodium dodecyl sulfate) onto treated membranes, which enabled preservation at ambient temperatures. A ready-mix of LAMP reagents, suitable for shipment at ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 17 publications
6
99
0
Order By: Relevance
“…mansoni DNA corresponding to less than the equivalent to one single miracidium or a single parasite cell. A high sensitivity has also been previously reported when using other LAMP assays to detect schistosomes in infected snails [10, 29], but a long time of 120 min was required to complete the reaction, whereas our LAMP assay ( Biompha -LAMP) takes only 50 min to obtain the same limit of DNA detection.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…mansoni DNA corresponding to less than the equivalent to one single miracidium or a single parasite cell. A high sensitivity has also been previously reported when using other LAMP assays to detect schistosomes in infected snails [10, 29], but a long time of 120 min was required to complete the reaction, whereas our LAMP assay ( Biompha -LAMP) takes only 50 min to obtain the same limit of DNA detection.…”
Section: Discussionsupporting
confidence: 74%
“…haematobium and S . mansoni [10] and potentially later adaptation in a large-scale screening of snails pooled samples to be used as method for snails control [28, 29]. The "development of inexpensive, field-applicable diagnostic assays for the large-scale screening of individual or pooled snails from transmission sites to detect the presence of schistosomes" has been listed as an important point to consider in an agenda for snail control interventions related to schistosomiasis elimination [30].…”
Section: Introductionmentioning
confidence: 99%
“…While these infection levels seem rather low considering the S. haematobium prevalence in children in the persistent hot-spot shehias, previous work conducted in Zanzibar has shown that the cercariae shedding method misses many prepatent infections [35]. If more advanced, molecular techniques are used for screening snails instead, it is likely to detect a considerably higher number of infected snails [35, 40, 4244]. Rapid detection of schistosome cercariae ribosomal DNA in environmental samples using new methods could also aid in uncovering transmission sites that may have previously been missed following classic snail ‘shedding’ methods [45].…”
Section: Discussionmentioning
confidence: 99%
“…Such procedures include molecular detection of S. mansoni cercariae in snail intermediate hosts [20], as well as assessment of current infection in human populations, through detection of antigens to S. mansoni (e.g. by circulating cathodic antigen (CCA) tests) [21, 22], or through stool sedimentation coupled with miracidia hatching test [23]. …”
Section: Resultsmentioning
confidence: 99%